Analysis Of The Effect Of Job Satisfaction And Tenure On Turnover Intention - Soeprapto, Adi; Tawil, Muhammad Risal; Naim, Sidrotun; Buamonabot, Irfandi; Thahrim, Muhammad (SEAN Institute, 2024)
This study aims to analyze the effect of job satisfaction and tenure on turnover intention. Using the survey method, data was collected from 30 employees from various industry sectors. Pearson correlation analysis showed that there is a significant negative relationship between job satisfaction and turnover intention (r = -0.527, p < 0.05), and between tenure and turnover intention (r = -0.382, p < 0.05). Multiple regression analysis shows that job satisfaction and tenure significantly affect turnover intention (p < 0.05), with a negative coefficient indicating that an increase in job satisfaction and tenure will decrease turnover intention. The interaction analysis shows that there is a significant interaction between job satisfaction and tenure in influencing turnover intention (p < 0.05). The results of this study provide insights for human resource managers to increase job satisfaction and retain long-term employees to reduce turnover intention. With the right strategies, organizations can improve employee retention and overall productivity.